Exploration of the Influence of Learning ELPSA (Experiences, Language, Pictures, Symbols, and Applications) on the Understanding of Mathematical Concepts - Herwandi, Herwandi; Kaharuddin, Andi (Indonesian Journal of Instructional Media and Model, 2020)
The ability of students to understand the concept of learning varies, it is very necessary to know the level of understanding of students' concepts in learning mathematics, so that it becomes a rationale in determining the appropriate learning approach. This study aims to determine the effect learning approach of the ELPSA eighth grade students of SMP Negeri 6 Makassar. The type of research used is experimental research. The design of this research is the One-Group Pretest-Posttest Design. The population in this study were students of class VIII SMP Negeri 6 Makassar in the 2019/2020 academic year and the research sample was determined by the Cluster Random Sampling technique. The instrument in this study was an essay test on understanding mathematical concepts. The data analysis used was descriptive and inferential. The descriptive research results show that there is an increase in understanding of the mathematical concept after the application of the ELPSA learning approach; the score of concept understanding after the application of the ELPSA learning approach met the completeness criteria, namely more than 80; and completeness of students' conceptual understanding after being applied classical ELPSA learning approach is 97% complete. The inferential hypothesis testing results show that the application of the ELPSA learning approach affects the understanding of mathematical concepts in class VIII students of SMP Negeri 6 Makassar.